2015
DOI: 10.1099/ijsem.0.000666
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium kavangense sp. nov., a symbiotic nitrogen-fixing bacterium from root nodules of traditional Namibian pulses

Abstract: Eight strains of symbiotic bacteria from root nodules of local races of cowpea (Vigna unguiculata) and Bambara groundnut (Vigna subterranea) grown on subsistence farmers' fields in the Kavango region, Namibia, were previously characterized and identified as a novel group within the genus Bradyrhizobium. To clarify their taxonomic status, these strains were further characterized using a polyphasic approach. In phylogenetic analysis of the 16S rRNA gene sequence the novel group was most closely related to Bradyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 24 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Nowadays, the suggested threshold for species delineation for the genus Bradyrhizobium using five concatenated genes is 97 % NI [22]. Several phylogenetic studies have suggested a minimum of four [6, 12], or even three [8] concatenated housekeeping genes in the MLSA, and a considerable number of Bradyrhizobium species have been described using four genes and an NI value of 97 % as the threshold for species delineation [2, 13, 33, 35, 36]. In our study, both sets of genes on the MLSA presented NI for the new groups compared with the most related species far below 97 %; the only exception was of group GII.III, which shared from 97 to 97.3 % NI with B.…”
Section: Phylogenymentioning
confidence: 60%
“…Nowadays, the suggested threshold for species delineation for the genus Bradyrhizobium using five concatenated genes is 97 % NI [22]. Several phylogenetic studies have suggested a minimum of four [6, 12], or even three [8] concatenated housekeeping genes in the MLSA, and a considerable number of Bradyrhizobium species have been described using four genes and an NI value of 97 % as the threshold for species delineation [2, 13, 33, 35, 36]. In our study, both sets of genes on the MLSA presented NI for the new groups compared with the most related species far below 97 %; the only exception was of group GII.III, which shared from 97 to 97.3 % NI with B.…”
Section: Phylogenymentioning
confidence: 60%
“…Comparison of the almost complete sequence (1268 nt) of the 16S rRNA gene of strain ESA 123 showed that this isolate is classified within the B. japonicum clade with the most similarity to the strain type 14-3 T B. kavangense. This species has recently been described, isolated from peanut nodules in Namibia (Grönemeyer et al 2015) and bacteria with sequences of the 16S rRNA gene related to B. kavangense were later isolated in South Africa (Jaiswal et al 2017) and in Brazil (Santos et al 2017a). Although the 16S rRNA gene sequence shows high similarity (98.97%) to B. kavangense, the ESA 123 strain may represent a new species, since the taxonomy of Bradyrhizobium is complex and cannot be elucidated only with the 16S rRNA allele (Hungria et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gronemeyer et al . [ 45 , 51 52 ] showed that Bradyrhizobium subterraneum , Bradyrhizobium kavangense and Bradyrhizobium vignae (all of African origin) are responsible for the nodulation of Bambara groundnut. However, from the phylogenetic analysis of individual and concatenated genes in this study, there were many unknown Bradyrhizobium species from Ghanaian and South African soils that nodulated Bambara groundnut, and are still waiting to be properly described.…”
Section: Discussionmentioning
confidence: 99%